The Effect of Provision Local Microorganisms of Corn, Bean Sprouts and Bamboo Shoots on the Growth of Sengon Seeds (Paraserianthes falcataria) - Demmanaba, Trialdi; Makmur (Pangale Journal of Forestry and Environment, 2021)
Quality seeds will be able to grow and develop quickly and give better results, soil fertility during the nursery process is very influential on the quality of seedlings, moles from bean sprouts and bamboo shoots contain growth regulators needed by plants. The purpose of this study was to look at the effect of the growth of sengon seeds from the provision of local microorganisms in the media of Corn, Bean Sprouts, and Rebung. The study used a Completely Randomized Design (CRD) with 8 treatments and 10 replications so that 80 experimental units were obtained. The results of this study indicate that the treatment of the sengon seedling media did not have a significant effect on the height, diameter and number of leaves of the sengon seedlings. The results showed height, diameter, number of leaves of sengon seedlings: mole of corn (26.4cm, 4.06mm, 65 strand), bamboo shoot mole (25.6cm, 3.76mm, 61 strand), bean sprouts (25.4cm, 4.35mm, 72 strand), control (25.2 cm, 4.08 mm, 70 strand), mole corn + bean sprouts (24.1 cm, 4.15 mm, 71 strand), Corn mole + bean sprout + bamboo shoot (23.8 cm, 4.12 mm, 60 strand), mole bean sprouts + bamboo shoots (23.5 cm, 4.10mm, 58 strands), and mole corn + bamboo shoots (22.3cm, 4.22mm, 66 strands), increase in height, diameter and number of leaves of sengon seedlings that are fertilized with those not fertilized (control) growth is not much different. Giving a mole dose of 20 ml / 1 L of water did not have a significant effect on the growth of sengon seedlings.